Patterns and Predictors of Prehypertension Among "Healthy" Urban Adults in India - Anand Chockalingam, N. Ganesan, S. Venkatesan, G. Gnanavelu, T. Subramaniam, V. Jaganathan, S. Elangovan, R. (Angiology 2005; 56; 557, 2005)
Cardiovascular disease is still on the increase in India owing to changing socioeconomic factors and unhealthy lifestyles. Better understanding of the role of hypertension (HTN) has led to new Joint National Committee (JNC-7) guidelines for its diagnosis and management. The authors aimed to evaluate the predictors and correlates of prehypertension (PreHTN) among adults in urban India. Study design is a cross-sectional survey among 2,007 adults in Chennai in July 2003; 1,505 men and 502 women over the age of 18 years were studied. Demographic data collected by direct interview were the following: age, smoking, alcohol intake, type of work, exercise patterns, and monthly income. Anthropometric data of height, weight, and waist and hip dimensions were measured. Blood pressure (BP) was recorded thrice, with at least 15 minutes between readings 2 and 3. The mean of readings 2 and 3 was taken for the study. Of the 2,007 people studied, 951 (47.4